Factors associated with hepatitis B vaccine series completion in a randomized trial for injection drug users reached through syringe exchange programs in three US cities. - Bowman, Sarah; Grau, Lauretta E; Singer, Merrill; Scott, Greg; Heimer, Robert (BMC public health, 2014)
Hepatitis B virus (HBV) is a vaccine preventable infection yet vaccination rates are low among injection drug users (IDUs) despite the high risk of infection and longstanding recommendations to promote vaccination. We sought to improve vaccination rates by reaching IDUs through syringe exchange programs (SEPs) in three U.S. cities.